The Ethical Dilemma of Public Administration in the Public Service Process - Yolanda Tatyana Silvia Yolanda; Rahmad Afri Ramdani; Andrea Puspita Cahyani (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Public services are all activities in order to fulfill basic needs in accordance with the basic rights of every citizen and resident of an item, service and / or administrative service provided by service providers related to the public interest. Communities as customers have needs and expectations in the performance of professional public service providers. The task of the Central Government and Regional Government is to provide public services that are able to satisfy the public. The implementation of decentralization and regional autonomy policies in Indonesia has resulted in regional governments having responsibility and authority in determining minimum service standards. The fundamental problems in the process of public service in Indonesia are about ethics. There is no universal standard on norms or ethics and sanctions that specifically regulate violations committed by the authorities in public services. Keywords : Public Service, Ethic, Norm